Conceptual Model of Collaborative Planning for Stunting Intervention in the Perspective of Sustainable Development Goals (SDGs) - Muhamad Taufiq; Muhamad Nur Afandi; Nor Suzylah Sohaimi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2025)
This paper proposes a conceptual model of collaborative planning for stunting intervention in the region. The study of stunting intervention is crucial because it is categorized as a global issue. The purpose of this study is to describe the collaboration process and develop a conceptual model of collaborative planning. The approach used in this study is a qualitative approach with Soft Systems Methodology (SSM) analysis tools to develop a conceptual model of collaborative planning. Data collection was conducted through semi-structured interviews, focus group discussions (FGDs), observations, and document studies. The results of the study are a conceptual model of collaborative planning as a solution for stunting intervention to determine the objectives and programs to be implemented by the regional government. Through the stages of this model, a collaborative process can be carried out with stakeholders. Environmental adaptation is needed to ensure the implementation of the conceptual model of collaborative planning runs smoothly. In other aspects, the socio-cultural diversity of the community has the potential to influence the collaborative process in collaborative planning.